2022
DOI: 10.3390/su14053071
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous ABA Enhances the Antioxidant Defense System of Maize by Regulating the AsA-GSH Cycle under Drought Stress

Abstract: When drought occurs during the maize-filling period, the probability of yield decline increases. Abscisic acid (ABA) plays a regulatory role in physiological and metabolic activities during plant development. However, its effect on the antioxidant system of maize leaves during the grain-filling stage is unclear. Maize plants (Zhengdan958) were used as an experimental material, and ABA was sprayed on the leaves during the grain-filling stage. The plants were placed under drought conditions to analyze the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Gly I, and Gly II are two-step MG-detoxification pathways that convert MG to D-lactate using glutathione as a co-factor. Our results are broadly in line with previous findings [11,18,19,28,29,85,86], whereas, BC application considerably improved the antioxidants in L. fusca roots and shoots.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gly I, and Gly II are two-step MG-detoxification pathways that convert MG to D-lactate using glutathione as a co-factor. Our results are broadly in line with previous findings [11,18,19,28,29,85,86], whereas, BC application considerably improved the antioxidants in L. fusca roots and shoots.…”
Section: Discussionsupporting
confidence: 93%
“…In wheat seedlings, it has been observed that the presence of AsA and GSH enhances osmoregulation, cellular water and nutrient status, photosynthetic rate, and overall plant growth and productivity [25,26]. Previous research showed that the AsA-GSH cycle helps plants regulate a number of physiological and molecular pathways in addition to scavenging ROS [25,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous ABA spraying has been shown in some studies to improve plant stress tolerance in various crop species. However, research evaluating the responses of different Zea mays L. and Glycine max L. to drought stress using exogenous ABA and fluoridone is severely limited (ABA synthesis inhibitor) [236,237]. ABA substantially enhanced the activities of SOD and POD during drought stress, with a considerable drop after re-watering [235].…”
Section: Abscise Acidmentioning
confidence: 99%
“…Hence, our results demonstrated that 6-BAP and ABA, both alone and in combination, significantly reduce H 2 O 2 , O 2 •− , TBARS, EL, SP, and LOX in the plants exposed to 100 µM Cd and 100 µM Cu. Numerous researchers have demonstrated the impact of 6-BAP and ABA on lipoperoxidation and ROS [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. One of the strategies employed by plants under heavy metal stress is to increase their cellular soluble protein, which can help to decrease the intracellular osmotic potential and provide the plants with normal water status as well as preserving the physiology process in the cell.…”
Section: Discussionmentioning
confidence: 99%